Geologic hazards : a field guide for geotechnical engineers - Hunt, Roy E. (CRC/Taylor & Francis, 2007)
Geologic hazards pose the greatest threat to human safety for any geotechnical undertaking, but it is ultimately the engineer's ability to recognize and cope with these hazards that will determine the safety of life and property. Armed with Geologic Hazards: A Field Guide for Geotechnical Engineers you will be able to properly recognize, understand various geologic hazards, and provide safe and economical construction. Eminent expert Roy E. Hunt thoroughly examines the potential for slope failures, earthquakes, ground subsidence, collapse, and expansion.
Keywords: Engineering geology -- Handbooks, manuals, etc.; Natural disasters.; elektronické knihy; electronic books